Assessment of physical violence against research assistants and nurses in an university hospital - Ogenler, Oya; Yapıci, Gulcin (Acta Bioethica, 2018)
The aim of this study was to determine the prevalence of physical violence and related factors among assistants and nurses. This cross-sectional study was included 166 research assistants and 209 nurses who worked at the University Hospital. The data was collected with a self-administered questionnaire. As 12.0% participants had a history of physical violence at workplace within the last 6 months. The perpetrator was a patient relative in 41 (78.8%) and the patient himself/herself in 18 (34.6%).The most common place of violence was emergency unit for the assistants and in-patient unit for the nurses. The emergency unit was observed to have a higher incidence of violence than other departments. One of every ten health care workers appears to be a victim of physical workplace violence. Between health care workers with patient/the relatives of the patient of the impact on relations the close of violence to be examined separately according to occupational groups. As a result, professional differences between nurses and doctors should be taken into consideration while investigating health violence. Each professions of healthcare have different professional practice and ethical obligations on the relationship between health care provider and patient /relatives.